Short Stories as a Pathway from Reading to Writing: Students’ Perceptions of English Language Improvement - Sevaraj Dhanalakshmi Srirevathi; Banumathi Rajamanickam Aravind (Acta Pedagogia Asiana, 2026)
Short stories were a successful teaching and learning strategy for second languages. This study aimed to find out how students felt about using short stories and how well they read and wrote English. The study intended to determine the advantages that students experienced from using short stories, as well as the difficulties they faced and how they overcame them. The study population consisted of secondary school students in Grade IX at a government tribal school in Tiruchirappalli District, who received instruction in Tamil (the regional language). A total of 40 students were selected using a sampling method. Constructivist theory provided the theoretical support for this investigation. The study employed a descriptive methodology, utilising focus group interviews and a questionnaire to gather data. While the focus group interviews produced qualitative data, the questionnaire generated quantitative data. The findings showed that the two English language skills, reading and writing, were developed among students through the use of short stories. The results also indicated that students’ vocabulary improved as a result of reading short stories. However, the findings revealed that students lacked confidence in sharing their experiences in front of their peers and struggled to understand messages due to limited resources, restricted vocabulary, spelling issues, and insufficient understanding of English tenses. Nevertheless, by learning new words and supporting one another’s learning, they were able to overcome these challenges. The study concluded that short stories were useful in enhancing language resources and could be proposed as effective materials for facilitating the acquisition of a foreign language.